Potensi Keanekaragaman Kepiting sebagai Bioindikator Kualitas Perairan di Pantai Tambakrejo, Blitar - Donna Laora Eka Febryana; Fauziah Naja Dwi Haryanti; Alisa Dwi Zhafira; Sabrina Brilianti Suhartono; Reni Ambarwati (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Crabs are a group of arthropod animals that play an important role as detritivors, keystone species, and bioindicators in a coastal ecosystem. This research aimed to describe the species, analyze diversity, relative abundance, uniformity, dominance, and the role of crabs as bioindicators of water quality at Tambakrejo Beach, Blitar. Data was obtained through on-site observation. Sampling was conducted using the purposive sampling method, and the sampling location was divided into three stations with different substrate characteristics. Data analysis used the Shannon-Wiener formula. The sampling results were identified and described based on morphological characters. The results found a total of 51 crabs classified into 7 crab species, namely Grapsus albolineatus, Ozius rugulosus, Metopograpsus thukuhar, Pachygrapsus marmoratus, Leptodius affinis, Ptychognathus barbatus and Parasesarma charis. The crab diversity index was recorded in the medium category, namely 1,873 and a uniformity index of 0,962 in the high category which indicates the distribution of the number of individuals of each genus is relatively uniform. The highest relative abundance in Hemigrapsus sanguineus species with a value of 23,53% and a dominance index of 0.164 or it can be said that in Tambakrejo Beach, Blitar there is no dominating crab species. Beaches with these characteristics have the potential for good water quality and are not polluted so that they can support the life of marine biota, especially crabs, and have potential in conservation efforts through maintaining water quality.